Application of Cooperative Learning Model Teams Games Tournament to Improve Mathematics Learning Outcomes in Grade VI Students of SDK Scriptura Bengel, Beo District, Talaud Islands Regency - Thofan Rame; Windhy C. Tulung; Angelina H. Semuruk (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The problem in this study is the low learning outcomes of mathematics in grade VI students of SDK Scriptura Bengel, Beo District, Talaud Islands Regency. To improve student learning outcomes in mathematics, it is necessary to apply cooperative learning model team games tournament. Cooperative learning model team games tournament is a learning model in which students are divided into study teams consisting of 4-5 people with different levels of ability, gender and ethnic background. Learning activities with games designed in cooperative learning. The Team Games Tournament (TGT) model allows students to learn more relaxed, foster responsibility, cooperation, healthy competition and involvement in learning. So that the application of cooperative learning with the teams games tournament model can improve mathematics learning outcomes for grade VI students of SDK Scriptura Bengel, Beo District, Talaud Islands Regency. The research was conducted on the sixth grade students of SDK Scriptura Bengel with 15 male students and 18 female students, the total is 33 students. The time of the research was carried out from October to December 2021. The research method used a classroom action research design (CAR) with several stages, namely Planning, Action Implementation, Observation and Reflection. Analysis of the data using the technique of complete learning outcomes (KB) with the formula: . The results of the research and discussion show that the application of the teams games tournament model of cooperative learning can improve mathematics learning outcomes from cycle I to cycle II. The results of learning mathematics through the material to determine the Least Common Multiple (KPK) with the application of cooperative learning model teams games tournament can improve student learning outcomes for grade VI SDK Scriptura Bengel.